Analyzing the Impact of Social Media on Humanities and Social Sciences Research Dissemination - I Putu Astawa; Krim Ulwi (Yayasan Adra Karima Hubbi, 2024)
Background. The development of digital technology, especially social media, has changed how information is disseminated and accessed. Social media is essential in communicating the results of humanities and social sciences research. However, the impact of social media on the effectiveness and reach of research dissemination in this area has yet to be studied. Purpose. This study aims to analyze the impact of social media on disseminating research in the humanities and social sciences. The focus is to evaluate how social media affects public reach, interaction, and acceptance of research results. Method. This study uses a mixed methods approach that combines quantitative and qualitative analysis. The quantitative data was collected through an online survey involving 300 humanities and social sciences researchers. Qualitative data were obtained through in-depth interviews with 20 selected researchers. Descriptive statistical analysis is used to identify patterns and trends, while thematic analysis is used to explore insights from interviews. Results. The results showed that social media significantly increased public reach and interaction with humanities and social sciences research. Researchers reported increased visibility and public engagement of their work through Twitter, Facebook, and LinkedIn platforms. However, there are also concerns about the quality of interactions and the risk of spreading inaccurate information. Conclusion. This study concludes that social media significantly impacts the dissemination of research in the humanities and social sciences, especially in increasing public reach and interaction. However, to maximize the benefits, appropriate strategies are needed to manage risks and ensure the quality of interactions. The study recommends developing guidelines and training for researchers to utilize social media effectively in disseminating their research results.